Evaluation index database and system for the ‘Beautiful Bay’ construction project - He Sun; Xingxing Guo; Shuang Xu; Ailing Yu; Chunyan Yu; Yan Xu (Marine Development)
Abstract Bays serve as economic development hubs, ecological protection areas, popular coastal sea-enjoyment destinations, and crucial geographical units, enhancing the marine ecological environment. In this study, we analyze international, national, and local marine evaluation research practices. Our results indicate that the design of the evaluation index database for the ‘Beautiful Bay’ construction project should include the main regions of ‘Beautiful Bay’ construction, focus on the ecological environment, connect with relevant index systems, and fully absorb local ‘Beautiful Bay’ construction index systems. To evaluate the effectiveness of ‘Beautiful Bay’ construction, we constructed an evaluation index database consisting of 64 evaluation indicators for 17 categories in five major fields. A unified evaluation index system with strong versatility can be used as a reference for local regions to implement their own ‘Beautiful Bay’ construction projects; additionally, it provides technical support for comprehensive, orderly, and high-quality promotion of the ‘Beautiful Bay’ construction project.